Effect of different application rates used by piloted aircraft on watermelon cultivation (Revista Brasileira Multidisciplinar, 2025)
Watermelon is one of the most cultivated vegetables in the world, however, the productivity and quality of the fruits are influenced due to the constant attack of pests and diseases. In this sense, the use of remotely piloted aircraft becomes a viable alternative. The objective of this study was to evaluate the effect of different application rates (8, 12 and 16 L ha-1) on the distribution of drops on different watermelon targets using a remotely piloted aircraft. Water-sensitive paper labels were used and placed on the targets of the watermelon tree (adaxial leaf, fruit and apical bud) for data collection. The results indicated that there was an increase in average values, as application rates increased in all watermelon targets, with a significant difference only for the lowest application rate (8.0 L ha-1). This study demonstrated, for the first time, the feasibility of using ARP in the possible application of phytosanitary products in watermelon cultivation.
Keywords: Unmanned aerial Vehicle; Citrullus lanatus L.; Efficiency; RPA; Application technology